Postgraduate students receive UMP Foundation Scholarship - Mimi Rabita, Abdul Wahit (2020)
Pekan, 14 July 2020 - UMP Foundation expanded their funds’ distribution with the introduction of scholarships for postgraduate students to aid students in paying for tuition fees and helping to cover expenses and pocket money while they undertake their education and research at Universiti Malaysia Pahang.